Pengaruh Digital Marketing, Persepsi Harga, Kualitas Pelayanan Terhadap Kepuasan Pelanggan Dalam Pembelian Online pada Belia Cosmetic Store (Studi Pada Mahasiswi Universitas Trunojoyo Madura) - Ariyanti, Monica Dea; Wantara, Pribanus (Jurnal Kajian Ilmu Manajemen (JKIM), 2024)
Indonesia, as a developing country, is a promising market. This situation shows that competition in the business world is currently increasingly intensive. Companies are expected to be able to hone their advantages and strengthen the positive reputation of their products in response to increasingly fierce competition, so that they can compete with other competitors. For example, the Belia Cosmetic store, which occupies the highest level based on online cosmetic store data, whose products are mostly purchased on Shopee. This requires strategies to defend the business from competitors. The aim of this research is to determine the influence of Digital Products, price perception, service quality on customer satisfaction in online purchases of Belia Cosmetic among students at Trunojoyo University, Madura. This research method uses quantitative methods. The data used are primary data and secondary data. Research data was obtained by distributing questionnaires using a Likert scale with a total of 100 respondents. This technique uses purposive sampling and the analysis method used in this research is Partial Least Square (PLS) 4.1.0.2 with outer model and iner model coefficient tests. The results of this research show that Digital Marketing has a significant effect on customer satisfaction and price perception has a significant effect on customer satisfaction. Meanwhile, the service quality variable has an effect on customer satisfaction but is not significant.